Using Audio-Visual Media to Improve Student Learning Outcomes in Science Learning - Sari, Ika Evitasari; Kartikasari, Cika (Jurnal Primagraha, 2021)
This research aims to determine the increase of learning outcomes of class IV students by using audiovisual media in SCIENCE subjects at SDN Unyur. The research used is class action research (PTK), using two cycles, consisting of several stages: planning, action, observation, and reflection. The results showed that the use of audio-visual media can improve the learning outcomes of IVB students in SDN Unyur. Student activity in pre-cycle 41% with less criteria then increased by 9% in cycle I with a percentage of learning outcomes of 50% with good criteria then increased again by 31% on cycle II with percentages Learning outcomes are 81% with excellent criteria. The average value in the Prasiklus 57,7 cycles I 70 and increased in cycle II 79,5. This proves that audiovisual media in SCIENCE learning with human sensory material can improve student learning outcomes.